PENGARUH PROMOSI DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN SURAT KABAR HARIAN SUARA MERDEKA - Muhammad Gigih Made; Rodhiyah Rodhiyah; Widiartanto Widiartanto (Jurnal Ilmu Administrasi Bisnis, 2015)
Consumer behavior is closely related to the purchase decision, the decision of the purchases made by individuals, groups and organizations in meeting their needs and desires both for goods and services. So it is very important for companies to understand how their consumers in their purchase decision, in order to influence the purchase decision. The purpose of this study was to determine the effect: promotion on purchasing decisions, the price of the purchase decision, promotions and prices on purchase decisions.The population of this study is the customer's Newspapers Suara Merdeka conducted in several sub-agents Semarang and surrounding many as   18.978 people. Sampling using slovin formula so that the number of samples used in this study as many as 100 people. Data were analyzed using test validity, reliability, simple linear regression analysis, multiple regression analysis, the coefficient of determination, t-test and F test calculation using the computer program SPSS version 19 for Windows.The results showed that: t value promotion variables (4.675) > t table (1.984), then Ho is rejected and Ha accepted means no influence between variables promotion on purchasing decisions, the value of the t variable price (12.249) > t table (1.984), then Ho is rejected and Ha accepted means no influence of price on purchase decision variables, variables calculated F value promotions and price (75.503) > F table (3.09), then Ho is rejected and Ha accepted means no influence of promotions and price variables to the decision purchase.In conclusion: there is a promotional effect on purchasing decisions, there is the effect of price on purchase decisions and there are promotions and prices influence on purchasing decisions. The advice given is: to increase and improve purchasing decisions can be done by continuously improving the creativity of the journalist as newsmakers, to enhance and improve the promotion, the efforts made by utilizing print and electronic media, for other researchers should conduct research about the factors that influence purchasing decisions by focusing on the elements of the marketing mix in addition to promotional and other prices are variable so that the distribution of products and research on marketing mix and purchasing decisions will be more perfect.